The effect of fabrication conditions on optical characteristics of CQDs prepared by micro plasma - Pham Van, Duong; Do Hoang, Tung; Pham Hong , Minh; Doan Thi, Kieu Anh; Binh, Nguyen Thanh (Vietnam Journal of Science and Technology, 2025)
Carbon quantum dots (CQDs) are emerging nanomaterials with outstanding advantages such as non-toxicity, high biocompatibility, and abundant functional groups, making them highly suitable for biological and optoelectronic applications. In this study, CQDs were synthesized using a solution-interaction microplasma method operated at atmospheric pressure. The obtained CQDs exhibit spherical morphology with particle sizes below 10 nm and demonstrate excitation-dependent fluorescence over the 350 - 650 nm wavelength range. The effects of fabrication parameters-including plasma electrode polarization, precursor concentration, and preparation time-on the optical properties of CQDs were systematically investigated. Variations in these conditions resulted in changes in fluorescence intensity, spectral width, and emission peak position, reflecting the strong dependence of optical behavior on surface states and structural features. The results confirm that microplasma synthesis enables effective tuning of CQD optical properties, providing insights into exciton self-trapped emission (EST) and supporting the development of environmentally friendly CQD-based fluorescent materials for potential display and sensing applications.